EVALUATION OF POTATO BASED CROPPING SEQUENCES UNDER DRIP, SPRINKLER AND FURROW METHODS OF IRRIGATION - Singh, Name; Sood, M. C; Lal, S. S. (Potato Journal, 2013)
Five cropping sequences evaluated at Meerut, revealed that the drip irrigation produced maximum potato equivalent yield (PEY) of 588.0 q/ha as compared to conventional furrow method of irrigation which produced 507.8 q PEY/ha. The sprinkler irrigation was found intermediate in category(561.6 q PEY/ha). In case of cropping sequences, the maize-potato-sunflower crop sequence produced maximum potato equivalent yields of 552.2, 595.2 and 625.3 q/ha in comparison to other cropping sequences tried under furrow, sprinkler and drip methods of irrigation, respectively. The yields of maize and bottlegourd were maximum as compared to other crops raised under different irrigation methods.